Impact of education quality on economic performance of countries - Erdoğan, Selin (My University, 2017)
Since economists Jacob Mincer, Theodore Schultz and Gary Becker coined and popularized the term human capital in the literature in 1960s, a lot of interest has been paid to the relationship between economic growth and human capital development. Educated individuals are more capable of having high income and more likely to contribute more to enterprises for which they work by means of increased productivity and hence to the country in which they live. At this point, it becomes obvious that effective role of human capital in an economy of a country is closely related to education because human capital could be invested and developed through education like any other type of physical capital investment. In this manner, this study aims to investigate the relationship between the education in both quality and quantity terms rather than a broad measure of educational quantity and economic performances of countries measured by real income per capita growth. More specifically, country mean scores achieved by students at Programme for International Student Assessment (PISA) and at Trends in International Mathematics and Science Study (TIMSS) are harnessed to proxy education quality. Cross sectional and panel analyses are conducted in order to investigate such a relationship and the empirical results from each analysis indicate evidence in favour of significant influence. According to cross-country empirical analysis, there is strong evidence for country mean scores at each subject of each test do have significantly positive impact on average annual growth rate of real income per capita. Based on the empirical analysis in panel framework indicate that although neither of country mean scores at any subject of PISA test is significant in the process of economic growth, TIMSS subject scores are significant in determining economic growth.

Ekonomistler Jacob Mincer, Theodore Schultz ve Gary Becker beşeri sermaye terimini literatüre kazandırdığı ve popülerleştirdiği 1960'lardan bu yana ekonomik büyüme beşeri sermaye ilişkisi araştırmacıların yoğun ilgisini çekmiştir. Eğitimli bireyler daha yüksek gelir elde etme imkanına sahiptir ve daha yüksek verimle çalışabildikleri için çalıştıkları firmalara ve dolayısıyla içinde yaşadıkları ülkeye daha çok katkıda bulunabilirler. Bu noktada şu oldukça açıktır: Beşeri sermayenin ülke ekonomisindeki etkin rolü eğitimle yakından ilişkilidir, çünkü beşeri sermaye tıpkı fiziki sermayeye yapılan yatırımlarda olduğu gibi eğitim yoluyla arttırılabilir ve geliştirilebilir. Bu anlamda, bu çalışma eğitim kalitesi ve miktarının sadece eğitim miktarından ya da seviyesinden ziyade- yıllık ortalama reel kişi başı milli gelir büyümesi ile arasındaki ilişkiyi incelemektedir. Eğitim kalitesi değişkeni ülkelerin PISA ve TIMSS testlerinde aldıkları ortalama puanlar aracılığıyla ölçülmüştür. Kesitsel ve panel veri analizlerinin kullanıldığı bu çalışmada iki analizden gelen ampirik sonuçlara göre ülkelerin uluslararası öğrenci değerlendirme testlerinde aldıkları puanlar kişi başı gelir büyüme oranı üzerinde anlamlı etkiye sahiptir. Kesitsel analizin sonuçlarına göre ülkelerin PISA ve TIMSS testlerinde aldığı ortalama puanlar yıllık ortalama kişi başı ekonomik büyüme üzerinde kuvvetli ve anlamlı pozitif etkiye sahipken, panel analizin sonuçlarına göre ise ülkelerin PISA testinde aldığı ortalama puanlar ülkelerin büyüme performansı üzerinde anlamlı bir etkiye sahip değilken, ülkelerin TIMSS testinde aldığı ortalama puanlar ülkelerin büyüme performansı üzerinde anlamlı etkiye sahiptir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2017
Keywords: Education quality; PISA; TIMSS; Economic growth; Eğitim kalitesi; Ekonomik büyüme